Feasibility of replacing 99mTc‐DTPA GFR measurements with eGFR from cystatin C in individuals with spinal cord injuries - Tatiana Kristensen; Peter S. Oturai; Bryan T. Haddock; Fin Biering‐Sørensen; Christina Kruuse; Ulrik B. Andersen (Physiological Reports)
Abstract In individuals with spinal cord injury (SCI) and neurogenic bladder dysfunction, guidelines recommend regular monitoring of kidney function by measuring the glomerular filtration rate using an externally administered filtration markers such as 99mTc‐DTPA, since creatinine‐based eGFR models are inaccurate due to lower muscle mass in these individuals. To examine the feasibility of substituting GFR measurements with eGFR based on s‐cystatin C, simultaneous 99mTc‐DTPA clearance (mGFR) and cystatin C‐based clearance (eGFRcys) measures were evaluated in 248 individuals with SCI. In a subgroup of 26 participants, the test–retest variability of eGFRcys was assessed. Finally, long‐term (1–3 years) repeatability of simultaneously measured mGFR and eGFRcys was evaluated in 40 individuals. We could demonstrate a very good correlation between mGFR and eGFRcys, with an intraclass correlation (ICC) of 0.92, a very good test–retest variation of eGFRcys (ICC: 0.98) and a very good long‐term repeatability of eGFRcys and mGFR (ICC 0.92 and 0.94, respectively). We conclude that in individuals with SCI, eGFR calculated from a single sample of cystatin C can replace measurements of GFR using an externally administered substance. Using a fixed normal limit rather than an age‐corrected normal material for p‐cystatin C or eGFRCYS will misclassify many individuals as having chronic kidney disease.